EXPLORING COLLEGE STUDENTS’ POTENCIES AND NEEDS IN EFL TRANSLATION CLASS - Hapsari, Anita Dwi; Irmayani, Irmayani (MEDIA DIDAKTIKA, 2024)
In order to give the lecturer with the necessary information to construct effective teaching practices for preparation, in-class activities, and evaluation, the capacities and requirements of students performing translation work should be determined as early as possible. With regard to the students’ interest, expectations, knowledge, abilities, and experience, among other factors, this preliminary study sought to determine the students’ capacities and requirements. The preliminary research participants were third-semester students enrolled in the English Language Education department of a university in Lamongan Regency, who planned to enroll in translation courses during the next three semesters. Through the use of both closed- and open-ended survey questions, the descriptive approach was used in this study. Based on a few theories of teaching and learning translation, such as those proposed by Duff (1994), Gile (1995), Tisgam (2009), Clavijo & Marin (2013), and Wang (2014), the data were examined. The data analysis’s elaborations primarily addressed the students’ capacities and requirements to acquire thorough and understandable explanations of the indicated components. Following data analysis, recommendations were made for how to create a teaching design that included instructional strategies, materials, kinds of practices, and evaluation.